Subcutaneous Quadrantectomy Is a Safe Procedure in Management of Early-Stage Breast Cancer - Lieto, Eva; Auricchio, Annamaria; Erario, Silvia; Sorbo, Giovanni Del; Cardella, Francesca (Frontiers in Surgery, 2022)
Background A less invasive surgery is often required today for many tumors, when oncologic radicality is strictly ensured, both in order to minimize hospital stay and health costs and to guarantee aesthetical results. Breast surgery for cancer is radically changed in the last years, since conservative interventions are widely performed everywhere. Methods The Authors present 75 cases of early breast cancer, randomly treated with standard quadrantectomy and subcutaneous quadrantectomy; the totally subcutaneous surgical technique implies only a short periareolar skin incision, and a complete quadrant resection with skin and subcutaneous layer preservation. Continuous data were analysed by unpaired student’s t test. The Chi square test was used to cumulate categorical variables. The Kaplan-Meyer method and long-rank test were used to compare Overal Survival and Disease Free Survival. Results No difference was found among the two groups in terms of type of tumor, Overal Survival, Disease Free Survival, early complications, radicality and mortality. The only significant differences were found both in lenght of hospital stay and in postoperative breast deformity that required a further intervention in some cases. Conclusions In the era of mini-invasive surgery and quality assurance, Authors conclude that subcutaneous quadrantectomy is a safe procedure that allows a less health cost and a better aesthetical result.